Non-invasive myocardial work is reduced during transient acute coronary occlusion - Sabatino, Jolanda (PLoS One, 2020)
BACKGROUND: During ischemia a close relationship exists between sub-endocardial blood flow and myocardial function. Strain parameters can capture an impairment of regional longitudinal function but are load dependent. Recently, a novel non-invasive method to calculate Myocardial Work (MW) showed a strong correlation with invasive work measurements. Our aim was to investigate the ability of non-invasive MW indices to identify the ischaemic risk area during transient acute coronary occlusion (TACO). METHODS AND RESULTS: The study population comprises 50 individuals with critical coronary stenosis (CCS). Echocardiography recordings were obtained before coronary angiography, during TACO and after revascularization to measure global longitudinal strain (GLS), Myocardial Work Index (MWI), Myocardial Constructive Work (MCW), Myocardial Wasted work (MWW), Myocardial work efficiency (MWE). Compared to baseline, we found a significant reduction of GLS (p = 0.005), MWI, MCW and MWE (p<0.001) during TACO. CONCLUSIONS: The non-invasive measurement of MW parameters is a sensitive and early marker of myocardial ischemia during TACO.